Analysis of Numeracy Literacy of SMP Negeri 5 Cimahi Class VII Students in Terms of Self-Efficacy - ., Wardono; Fathurrohman, Fani Laffanillah; Mariani, Scolastika; Wijayanti, Kristina; Nuswowati, Murbangun; Agoestanto, Arief (Journal of Ecohumanism, 2024)
This study aims to analyze numeracy literacy in terms of self-efficacy. This research is descriptive qualitative research with the subjects as many as 40 students of class VII-D SMP Negeri 5 Cimahi. The research subjects were selected using purposive sampling technique by classifying the self-efficacy scale (high, medium, and low), 1 student each was taken so that the number of research subjects was 3 out of 40 students. The findings of this study indicate that in the first case, 1 student with a high self-efficacy category showed very capable in all indicators. The next case, 1 student with a moderate self-efficacy category showed quite capable, still not able to analyze information, while the third case, 1 student with a low self-efficacy category showed not able to interpret the results of the analysis to predict and make decisions, and only able to analyze information displayed in various forms (graphs, tables, diagrams, and so on).